HUBUNGAN REGULASI DIRI DENGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS KRISTEN SATYA WACANA - Jessica Aurellia ,; Heru Astikasari Setya Murti , (Journal of Innovation Research and Knowledge, 2024)
The development of information and technology has given rise to social media which has now become part of various levels of society, especially young people such as students. The emergence of social media is accompanied by positive and negative impacts which is lead to an urgency to reduce the intensity of its use, one of which is by setting self-regulation. This research aims to determine the relationship between self-regulation and the intensity of social media use among students at the Faculty of Psychology, Universitas Kristen Satya Wacana. This research is quantitative research, where data collection was carried out by distributing questionnaires to 150 respondents. The correlation test results show that there is a relationship between self-regulation and the intensity of social media use, where the correlation coefficient of 0.273 is positive, indicating the relationship is at a weak level. The results of data categorization show that respondents' self-regulation is in the medium category as much as 56% and in the high category as much as 44%. Meanwhile, the intensity of social media use in the low category was 2%, in the medium category was 86.7%, and in the high category was 11.3%.